2020
DOI: 10.3382/ps/pez512
|View full text |Cite
|
Sign up to set email alerts
|

Impact of galactooligosaccharides delivered in ovo on mitigating negative effects of heat stress on performance and welfare of broilers

Abstract: Galactooligosaccharides (GOS) delivered in ovo improve intestinal health of broiler chickens. This study aimed to demonstrate the impact of in ovo stimulation with GOS prebiotic on day 12 of egg incubation on performance and welfare traits in broiler chickens. The incubating eggs were divided into 3 groups, based on the substance injected in ovo: 3.5 mg of GOS dissolved in 0.2 mL physiological saline (GOS), 0.2 mL physiological saline (S), or uninjected controls (C). Constant heat stress (HS) was induced on da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 40 publications
2
45
0
Order By: Relevance
“…Studies conducted by Yalcin et al [8] showed that 3 weeks of heat treatment (32 to 35 • C/7 h/day) reduced the body weight gain in chickens. A previous study reported that in ovo injection of galactooligosaccharides could maintain the body weight during heat stress [19]. However, the CH and HH groups showed a lower body weight gain than the control group, that showed the early heat exposure have no effect on body weight (Table 4).…”
Section: Discussionmentioning
confidence: 88%
“…Studies conducted by Yalcin et al [8] showed that 3 weeks of heat treatment (32 to 35 • C/7 h/day) reduced the body weight gain in chickens. A previous study reported that in ovo injection of galactooligosaccharides could maintain the body weight during heat stress [19]. However, the CH and HH groups showed a lower body weight gain than the control group, that showed the early heat exposure have no effect on body weight (Table 4).…”
Section: Discussionmentioning
confidence: 88%
“…On a performance level, HS causes losses in feed intake and growth rate. In broiler chickens, chronic HS has been found to significantly reduce (p < 0.01) final body weight (BW) (2.52 kg in TN vs. 3.11 kg in HS) [32,39,40]. In the current study, chronic HS also reduced final BW (p < 0.001), but the difference between TN and HS was almost two times lower than in broiler chickens (2.21 kg in TN vs. 1.94 kg in HS), even with the longer rearing period (42 days in broilers vs. 50 days in slow-growing chickens).…”
Section: Stress-related Gene Expression Signaturesmentioning
confidence: 99%
“…Galactooligosaccharides are potent prebiotics that exert beneficial effects on intestinal microbiota in chickens. Particularly interesting is the possibility of using in ovo technology for the early stimulation of the microbial communities with GOS [32,39,40]. The molecular data on broiler chickens have indicated that HS triggers systemic immune and stress responses, which are balanced by GOS that are delivered in ovo [41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects were alleviated by GOS delivered in ovo, most likely due to maintaining intestinal eubiosis [80]. Furthermore, GOS delivered in ovo mitigated harmful effects of chronic heat stress on the performance and welfare of broiler chickens [81], as well as meat composition and quality [82].…”
Section: Immunomodulatory Role Of Gosmentioning
confidence: 99%